43 lecturers accidentally 'imprisoned.'. (Times Higher Education, 2008)
The article reports on what was described by Mike Adobe, Deputy Head of Advanced Computer Services at Poppleton University in England, as a technological blip that led to the accidental overnight retention in the Central Library of 43 members of the academic staff in October 2008. The incident occurred when the staff members entered the library using their 6.22.1 bar-coded staff cards, not knowing that these were replaced by the new 6.22.2 cards. Elizabeth Parteger of the Department of Medieval Studies for Business described the experience as traumatic.